Building capacity of librarians for knowledge and skill development: a case study of nine institutions of the consortium for advanced research training in Africa (CARTA) (2014)
Librarians have an important part to play in supporting research, training and developing the knowledge economies of nations. The changing roles of librarians and the attendant new skills and knowledge required to play these roles are a major challenge for libraries and librarians in developing countries, especially those in Africa. To meet this challenge, the Consortium for Advanced Research Training in Africa (CARTA) seeks to promote development through advanced research training. In achieving this vision, librarians need to be empowered with knowledge and skills required to support teaching, learning and research in the continent. This is being implemented through the Consortium of CARTA Libraries (CCL), an alliance under CARTA, that aims to strengthen capacity and promote collaboration among librarians and libraries from CARTA institutions.